PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE TERHADAP PRAKTIK MANAJEMEN LABA DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Patricia Elisabeth Simanjuntak; Abdul Rohman (Diponegoro Journal of Accounting, 2026)
This study aims to determine the relationship between Environmental, Social, and Governance (ESG) disclosure and earnings management practices moderated by firm size. Sustainability reporting disclosure can be a corporate strategy to attract the attention of stakeholders and gain legitimacy from the public, thereby suppressing earnings management practices. This study involves Environmental, Social, and Governance (ESG)as the independent variable, earnings management as the dependent variable, firm size as the moderating variable, and return n assets as the control variable.The population in this study consisted of companies in the manufacturing and energy sectors listed on the Indonesia Stock Exchange in 2021-2024. Sampling was conducted using purposive sampling, resulting in a total of 186 research samples. The analysis method used in this study was panel data regression analysis processed using Eviews 12.  The findings of this study indicate that ESG disclosure is unable to suppress earnings management practices and that firm size has a positive effect on earnings management when controlled by return on assets. In addition, this study also proves that firm size cannot moderate the relationship between ESG and earning management.